Strategies for establishing harmony in Javanese face-to-face dialog in Purwa Shadow Puppet Performances - Rahmawanto, Dwi; Rahyono, F.X. (Penerbit Universiti Kebangsaan Malaysia, 2019)
Harmony is a critical Javanese philosophical concept used to establish social relationships. In face-to-face communication, the principle of harmony is enacted in an attempt to ensure the social relations between the speakers remain harmonious, peaceful, and free from disputes. In face-to-face discourse, the selection of speech acts that establishes these aspects is a strategic communication tool. Every speech act states a different level of politeness when addressed to different speech partner. Wayang kulit, a leading puppet theater performance of the Javanese, contains face-to-face dialogs that enact such efforts to maintain harmony. This study examines these dialogs between wayang kulit characters to better understand the role that language plays in establishing harmony in this art form of puppet theater. The study uses the classification of speech acts by Searle (1975). It is observed that the choice of illocutionary speech acts plays a role in controlling the occurrence of disputes in communication. These speech acts are also studied from the perspective of the theories of politeness from Brown and Levinson (1978) and Leech (1983); (2014). We argue that politeness in speech is used to express the values of Javanese harmony. The results of this study provide practical insight into the principle of Javanese harmony, represented in face-to-face communication in a purwa shadow puppet performance, and also represents a universal value appropriate for the realization of friendly social relationships more broadly.